Applying Evidence-Centered Design to Measure Psychological Resilience: The Development and Preliminary Validation of a Novel Simulation-Based Assessment Methodology - Kleitman, Sabina; Jackson, Simon A.; Zhang, Lisa M.; Blanchard, Matthew D.; Rizvandi, Nikzad B.; Aidman, Eugene (Frontiers in Psychology, 2022)
Modern technologies have enabled the development of dynamic game- and simulation-based assessments to measure psychological constructs. This has highlighted their potential for supplementing other assessment modalities, such as self-report. This study describes the development, design, and preliminary validation of a simulation-based assessment methodology to measure psychological resilience—an important construct for multiple life domains. The design was guided by theories of resilience, and principles of evidence-centered design and stealth assessment. The system analysed log files from a simulated task to derive individual trajectories in response to stressors. Using slope analyses, these trajectories were indicative of four types of responses to stressors: thriving, recovery, surviving, and succumbing. Using Machine Learning, the trajectories were predictive of self-reported resilience (Connor-Davidson Resilience Scale; Connor & Davidson, 2003) with high accuracy, supporting construct validity of the simulation-based assessment. These findings add to the growing evidence supporting the utility of gamification in assessment. Importantly, these findings address theoretical debates about the construct of resilience, adding to its theory, supporting the combination of the ‘trait’ and ‘process’ approaches to its operationalization.